Implementation of Group Discussion Learning Method Through The Two Stay Two Stray Learning Model to Student of Elementary School 10 South Rantau Labuhan Batu - Rahma Ritonga; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
The application of the Two Stay Two Stray learning model can help students become more active during learning and better master the problems discussed. Two Stay Two Stray is a cooperative learning model that provides an opportunity for groups to share results and information with other groups. This model teaches students to actively discuss in groups and work together to discuss a problem. In this cooperative learning, learning groups are formed heterogeneously, both in terms of academic ability, gender, race, ethnicity, and so on, so that each group member can help each other, both in receiving and providing assistance. The emphasis is not only on completing tasks, but also on developing interpersonal relationships that are mutually respectful. Based on the results of the study, discussion activities using the Two Stay Two Stray learning model showed maximum results. Students showed significant improvements in aspects of courage, enthusiasm, clarity of speech, and sentence structure during discussions. They were also able to express opinions accompanied by rational reasons. The improvement in discussion results can be seen from the comparison of students' abilities before and after the implementation of the action. At the pre-action stage, students' discussion ability scores were still relatively low. Students looked passive, shy, and less active in discussions. They also lacked the courage to convey ideas or arguments and were less fluent in speaking. After being subjected to the action, students' abilities increased significantly. The results of this study indicate that the Two Stay Two Stray learning model has a positive influence on group discussion skills in the Indonesian Language subject. This model is effective in improving the discussion skills of fifth grade students of SD Negeri 10 Rantau Selatan, Labuhan Batu Regency, 2025-2026 Academic Year